Preferential flow under high‐intensity short‐duration irrigation events in soil columns from a karst and nonkarst landscape - Sheela Katuwal (Wiley, 2021)
Abstract Preferential flow through soil macropores is a major cause of rapid transport of contaminants through soils to drainages systems. Knowledge of the extent of macropore flow in different soil systems is crucial for the effective implementation of nutrient management plans. The objective of this study was to determine the differences in preferential flow in soil columns characterized by varying contents of coarse fragments with depth and obtained from a regional, pasture‐based karst and a nonkarst landscape. Intact soil columns (40 × 100 cm; two replicates per treatment) were subjected to two Brˉ leaching experiments (BL1 and BL2) which included a pulse application of Brˉ tracer solution (3.02 and 1.15 g L−1 during BL1 and BL2, respectively), each followed by five successive irrigation events (5.67 mm min−1 for 2 min in 30‐min intervals). Each soil column rested on a stainless‐steel grid (consisting of 100 cells, each measuring 3.81 cm × 3.81 cm), which facilitated partitioning of the soil bottom and collection of drainage from each grid. Significant differences in the drainage losses of water and Brˉ through the 1‐m‐deep soil profiles were observed with karst‐derived stony soils draining approximately five times greater water and Brˉ, compared with nonkarst‐derived soil. These results suggest that soils with high fraction of coarse fragments are more susceptible to leaching losses than soils with less coarse fragments. Further studies under different flow regimes and encompassing different soil units may be beneficial in understanding the potential leaching risk in these areas and for implementing best management practices for landscape‐based nutrient management.